2019
DOI: 10.1002/eng2.12061
|View full text |Cite
|
Sign up to set email alerts
|

One‐step preparation of organic‐inorganic hybrid capsules based on simultaneous gelation and silicification

Abstract: Enzyme encapsulation within alginate capsules usually suffers from low encapsulation efficiency and leakage of enzyme. In this study, alginate‐aminosilane hybrid capsules with high encapsulation efficiency, good retention and high storage stability of enzyme have been prepared by a novel method, in which viscous solution containing enzyme, calcium chloride as a crosslinker, and 3‐(2‐aminoethylamino)propyltrimethoxysilane as an aminosilane was dripped into alginate solution, facilitating the formation of algina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…These results confirmed that solid alginate hydrogel beads are more suitable as carriers for the immobilization of g-C 3 N 4 . In previous studies in which g-C 3 N 4 was immobilized in alginate hydrogels, even under optimal conditions, the degradation of RhB (10 ppm) took 3–36 h. 33,34 Neither study formed heterojunctions in g-C 3 N 4 , which did not improve the charge separation problem. Hao et al added a higher concentration of g-C 3 N 4 (15% w/v) to the alginate solution, 36 which would have resulted in a higher photocatalyst content per bead and poor light penetration inside the beads.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…These results confirmed that solid alginate hydrogel beads are more suitable as carriers for the immobilization of g-C 3 N 4 . In previous studies in which g-C 3 N 4 was immobilized in alginate hydrogels, even under optimal conditions, the degradation of RhB (10 ppm) took 3–36 h. 33,34 Neither study formed heterojunctions in g-C 3 N 4 , which did not improve the charge separation problem. Hao et al added a higher concentration of g-C 3 N 4 (15% w/v) to the alginate solution, 36 which would have resulted in a higher photocatalyst content per bead and poor light penetration inside the beads.…”
Section: Resultsmentioning
confidence: 86%
“…33 Alginate capsules with a hard outer shell and viscous core were synthesized via addition of a viscous solution containing the crosslinker and catalyst into an alginate solution. 34 By encapsulating g-C 3 N 4 in hydrogel beads or capsule, the operability of g-C 3 N 4 in practical and large-scale applications is improved and possible nanopollution is prevented, increasing the potential for commercialization. 25,35 Although two such cases of g-C 3 N 4 immobilization in alginate beads and capsules have been reported, their photocatalytic activities are low and further improvement is required to apply for practical application.…”
Section: Introductionmentioning
confidence: 99%